A nationwide register study of the characteristics, incidence and validity of diagnosed Tourette syndrome and other tic disorders. (1st August 2014) - Leivonen, Susanna; Voutilainen, Arja; Hinkka‐Yli‐Salomäki, Susanna; Timonen‐Soivio, Laura; Chudal, Roshan; Gissler, Mika; Huttunen, Jukka; Sourander, Andre
Abstract Aim The aim of this study was to describe the characteristics and incidence rates of diagnosed tic disorders in the Finnish Hospital Discharge Register, including changing incidence rates between 1991 and 2010. We also aimed to validate the diagnoses of Tourette's syndrome recorded in the register. Methods Children born between January 1, 1991 and December 31, 2010, who were diagnosed with tic disorders, were identified from the Finnish Hospital Discharge Register (n = 3003). We studied the validity of the Tourette's syndrome diagnoses by reviewing the medical charts of 88 children born since 1997 and carrying out telephone interviews with 55 of their guardians. Results The incidence rates of all diagnosed tic disorders increased during the study period. A comorbid diagnosis of hyperkinetic disorder diagnosis was recorded in 28.2% of the children with Tourette's syndrome, and the validity of the register‐based Tourette's syndrome diagnosis was approximately 95%. Conclusion This is the first nationwide study to demonstrate the increasing incidence of all register‐based tic disorder diagnoses. The validity of the Tourette's syndrome diagnoses in the Finnish Hospital Discharge Register was good, and the data provided are suitable for use in further register‐based studies of tic disorders.